Attribution-based motivation treatment efficacy in high-stress student athletes: A moderated-mediation analysis of cognitive, affective, and achievement processes. (March 2018) - Parker, Patti C.; Perry, Raymond P.; Hamm, Jeremy M.; Chipperfield, Judith G.; Hladkyj, Steve; Leboe-McGowan, Launa
Abstract: Objectives: Student athletes encounter significant challenges during school-to-college transitions that can increase stress and undermine academic adjustment (Heelis & Shields, 2015 ). An attribution-based motivation treatment (Perry et al., 2014 ) was administered to student athletes who differed in perceived stress to improve short- and long-term academic performance. Methods: In a two-semester, quasi-experimental, randomized treatment study, we examined the efficacy of an attribution-based motivation treatment (Attributional Retraining; AR) for competitive student athletes ( N  = 185) who differed in perceived stress (low, high). A theory-based path analysis assessed whether AR-performance effects were mediated by perceived academic control (PAC) and achievement emotions. Results: High-stress student athletes who received AR outperformed their no-treatment counterparts by roughly one letter grade on a Semester 1 post-treatment class test. Consistent with Weiner's attribution theory (1985, 2012) of motivation and emotions, AR-performance effects were mediated by cognitive and affective process variables. For high-stress athletes, AR fostered course-related PAC, which in turn increased positive and reduced negative affect, which in combination promoted final course grades. Conclusions: AR effects on performance for high-stress student athletes were indirect via cognitive and affective mediators consistent with Weiner's attribution theory (1985, 2012). Findings suggest attribution-based motivation treatments have practical implications for athletic programs, administrators, coaches, and directors in facilitating adjustment for high-stress student athletes. Highlights: A motivation treatment (Attributional Retraining) was delivered to college athletes. AR promoted post-treatment course test scores for high-stress athletes only. AR's effects on final grades were mediated by cognitive and affective processes. Perceived stress moderates the AR→perceived control→emotions→performance sequence.